THE ONTOLOGICAL NATURE AND DISCURSIVE DYNAMICS OF PHRASEOLOGICAL UNITS VS LEXICAL UNITS - Bozorov Behruz Ilhom oʻgʻli (Bright Mind Publishing, 2026)
This paper provides a comprehensive linguistic analysis of the structural, semantic, and pragmatic distinctions between words and phraseological units (idioms). While words serve as the primary denominative tools of language, phraseological units function as complex semiotic signs characterized by stability and semantic opacity. The study explores why idioms are indispensable in modern communication, focusing on their cognitive-metaphorical roots and their role in communicative economy.